Spatial and Annual Temporal Distribution of Ozone Concentrations in the Madrid Basin Using Passive Samplers - M.J. Sanz; F. Sanz; G. Sanchez-Peaa (The Scientific World Journal)
Passive samplers are useful tools for helping to describe the ozone distribution in complex terrain situations. They are also a good complement to continuous monitoring stations. This paper discusses the results of a pilot study that used ozone passive samplers to describe the spatial and annual temporal distribution of ozone in several forested areas around the city of Madrid. The ozone concentrations around Madrid were found to be higher on the elevated sites located at a certain distance from the citys urban zone. A seasonal ozone cycle was observed, with maximum concentrations found in the basin in late spring or summer depending on the location. The information obtained allowed us to group the locations into four classes. Altitude and distance to the city during the summer and winter explained the observed ozone concentrations. However, during the transition periods, especially in early spring and to a lesser extent in autumn, there was not a good correlation between ozone levels and elevation or distance from precursor sources. These data strongly suggest that altitudinal gradients for ozone are not always the case in the Madrid Basin.